2022
DOI: 10.1088/1742-6596/2175/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of epoxidation levels on curing characteristic and mechanical properties of ENR/MFC composites

Abstract: This study aimed to investigate the effect of epoxidation levels on the curing and tensile properties of epoxidized natural rubber (ENR)/microfibrillated cellulose (MFC) composites. ENRs with different levels of epoxidation were first prepared from natural rubber (NR) latex via ‘in situ’ performic epoxidation using 0.75 M formic acid and 1 M hydrogen peroxide at 50°C at various reaction times. The results from H1 NMR revealed that the reaction at 2, 4, and 6 hours could achieve 20, 30, and 40 mol % epoxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…This result is in excellent agreement with Bhakri et al, which reported a remarkable modulus increase of ENR by incorporating microfibrillated cellulose as fillers. 45 The results of the hardness tests illustrate the effects of filler concentration and chemical interactions within the composite as shown in Fig. 6(c).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…This result is in excellent agreement with Bhakri et al, which reported a remarkable modulus increase of ENR by incorporating microfibrillated cellulose as fillers. 45 The results of the hardness tests illustrate the effects of filler concentration and chemical interactions within the composite as shown in Fig. 6(c).…”
Section: Resultsmentioning
confidence: 80%
“…This result is in excellent agreement with Bhakri et al , which reported a remarkable modulus increase of ENR by incorporating microfibrillated cellulose as fillers. 45…”
Section: Resultsmentioning
confidence: 99%